Big-fish-little-pond effect on academic self-concept: A reply to responses - Marsh, H (2005)
The purpose of this article is to reply - within the designated length limitation - to three invited responses to my (Marsh, 2005) overview of the big-fish-little-pond effect (BFLPE). In its simplest form, the BFLPE predicts that equally able students have lower academic self-concepts when attending schools or classes where the school-average ability levels of classmates is high, and higher academic self-concepts when attending schools where the school-average ability is low. None of the three responses to Marsh (2005) argues against the basic theoretical and empirical research in support of the BFLPE - that school-or class-average ability has a negative effect on academic self-concept. However, each of the three responses - coming from very different perspectives - proposes new questions and addresses broader implications that provide a rich basis for further BFLPE research in Germany and throughout the world. © Verlag Hans Huber, Bern.